2014
DOI: 10.1083/jcb.201309119
|View full text |Cite
|
Sign up to set email alerts
|

PP2ARts1 is a master regulator of pathways that control cell size

Abstract: PP2ARts1 controls diverse pathways that influence cell size and may link cell cycle entry to cell growth via the transcription factor Ace2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 82 publications
(168 reference statements)
4
96
1
Order By: Relevance
“…In addition, the temperature sensitivity of rts1D is partially suppressed by swe1D ( Figure S1A). The increase in Cdk1-Y19 phosphorylation in these mutants and their interaction with mih1D can at least be partially attributed to upregulation of Swe1 protein in both cdc55D and rts1D cells (Minshull et al 1996;Harvey et al 2011;Zapata et al 2014) and downregulation of Mih1 in cdc55D cells (Pal et al 2008), but it also may be caused by other functions of PP2A.…”
Section: Ptp1 Regulates Cdk1 Tyrosine Dephosphorylationmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, the temperature sensitivity of rts1D is partially suppressed by swe1D ( Figure S1A). The increase in Cdk1-Y19 phosphorylation in these mutants and their interaction with mih1D can at least be partially attributed to upregulation of Swe1 protein in both cdc55D and rts1D cells (Minshull et al 1996;Harvey et al 2011;Zapata et al 2014) and downregulation of Mih1 in cdc55D cells (Pal et al 2008), but it also may be caused by other functions of PP2A.…”
Section: Ptp1 Regulates Cdk1 Tyrosine Dephosphorylationmentioning
confidence: 95%
“…In addition, the temperature sensitivity of rts1D is partially suppressed by swe1D ( Figure S1A). The increase in Cdk1-Y19 phosphorylation in these mutants and their interaction with mih1D can at least be partially attributed to upregulation of Swe1 protein in both cdc55D and rts1D cells (Minshull et al 1996;Harvey et al 2011;Zapata et al 2014) and downregulation of Mih1 in cdc55D cells (Pal et al 2008), but it also may be caused by other functions of PP2A.To test whether PP2A regulates Cdk1-Y19 phosphorylation independently of its function regulating Swe1 and Mih1, we developed an in vivo phosphatase assay in which we monitor Cdk1-Y19 dephosphorylation in mitotically arrested cells that first induce high levels of Swe1 and Cdk1-Y19 phosphorylation using galactose induction of a GAL-SWE1-AID gene, then rapidly repress SWE1 transcription with glucose, and degrade the Swe1-AID protein with the addition of auxin (Figure 2). This experimental design allows us to assess the role of PP2A independently of its function regulating Swe1 and in the absence of Swe1-dependent rephosphorylation of Cdk1.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, proteomewide mass spectrometry studies have found that all three of the Gin4-related kinases are strongly hyperphosphorylated on multiple sites in rts1∆ cells, and that synthesis of ceramides influences Gin4 phosphorylation (Zapata et al 2014;Lebesgue et al 2017).…”
Section: Elm1 and The Gin4-related Kinases Do Not Influence Torc2 Sigmentioning
confidence: 99%